Aplikasi Metode Penerjemahan dalam Pembelajaran Kitab Kuning - Ainur Rohmah; Muhammad Muklas (Titian Ilmu: Jurnal Ilmiah Multi Sciences, 2018)
Translation as a process cannot be separated to the activity in foreign language learning despite there is still a controvesial issue abou it. This article aims to describe the translation process in Bandongan and Sorogan Method as the oldest and the best method in teaching and learning “kitab kuning”. The data are collected by observing, interviewing and studying of documentation. The writer as an instrument to collect the data attended the teaching and learning process. The data are analyzed by comparing the theory of translation method and the application of bandongan and sorogan method. The result shows that in the bandongan method, the teacher apply the word for word and literal method toward text in kitab kuning and also in sorogan method, the students apply word for word and literal method when they are reading kitab kuning.